PALAEOCLIMATE ANALYSIS OF LATE CRETACEOUS ANGIOSPERM LEAF FLORAS, JAMES ROSS ISLAND, ANTARCTICA - Hayes P.A.; Francis J.E.; Cantrill D.J.; Crame J.A. (My University, 2006)
The fossilized remains of Cretaceous angiosperm leaves are preserved within sandstones and siltstones of the Coniacian Hidden Lake Formation (Gustav Group) and the Santonian-early Campanian Santa Marta Formation (Marambio Group) in the James Ross Basin, Antarctic Peninsula region. The leaves represent the remains of vegetation that grew at approximately 65°S on an emergent volcanic arc, now represented by the Antarctic Peninsula, and were subsequently transported and buried in marine sediments in the adjacent back-arc basin. Some of the angiosperm leaf morphotypes show similarities to leaves of living families such as Sterculiaceae, Lauraceae, Winteraceae, Cunoniaceae and Myrtaceae. Palaeoclimate analysis based on physiognomic aspects of the leaves, such as leaf-margin analysis, indicates that the mean annual temperatures for the Hidden Lake and Santa Marta formations were 13-21 °C (mean 17 °C and 15-23 °C (mean 19 °C), respectively. The fossil plants are indicative of warm climates without extended periods of winter temperatures below freezing and with adequate moisture for growth. This period of Cretaceous warmth in Antarctica corresponds with the Cretaceous thermal maximum, an interval of peak global warmth from the Turonian to the early Campanian. © The Geological Society of London 2006.
Keywords: Campanian; Santonian; Coniacian; Turonian; Mesozoic::Cretaceous::Upper::Campanian; Мезозой::Меловая::Верхний::Кампанский; Mesozoic::Cretaceous::Upper::Santonian; Мезозой::Меловая::Верхний::Сантонский; Mesozoic::Cretaceous::Upper::Coniacian; Мезозой::Меловая::Верхний::Коньякский; Mesozoic::Cretaceous::Upper::Turonian; Мезозой::Меловая::Верхний::Туронский